Characterization of the interaction between P3ATs with PCBM on ITO using in situ Raman spectroscopy and electrochemical impedance spectroscopy - Bento, Danielly Cristina; da Silva, Edilene Assunção [UNESP]; de Almeida Olivati, Clarissa [UNESP]; Louarn, Guy; de Santana, Henrique (Springer Nature, 2015)
In this study, phenyl-C61-butyric acid methyl ester (PCBM) was deposited onto indium tin oxide (ITO) using the Langmuir–Schaefer technique, and poly(3-methylthiophene) (P3MT) and poly(3-hexylthiophene) (P3HT) were then electrochemically synthesized onto the ITO/PCBM, producing PCBM/P3MT and PCBM/P3HT films respectively. These films are widely used to create heterojunctions in organic photovoltaic cells, and they were produced in this study in order to monitor the charge transfer process between the P3ATs and PCBM. Cyclic voltammetry (CV) of the ITO/PCBM/P3AT systems demonstrates dislocation of oxidation and reduction peaks and a variation in the current of these peaks in relation to those observed in ITO/P3ATs. Charge transfer resistance (RCT) were determined using electrochemical impedance spectroscopy (EIS) to produce Nyquist plots at open circuit potential and at different applied potentials. ITO/PCBM/P3HT had a lower RCTvalue than ITO/P3HT and ITO/PCBM/P3MT. Bode phase plots produced using EIS indicated that the charge transfer process in ITO/PCBM/P3HT is associated with polaron conduction (radical cation) and in ITO/PCBM/P3MT with bipolar conduction (dication). This study of the behaviour observed in these systems using CV and EIS techniques was supplemented with ex situ and in situ Raman spectroscopy. Structural variations were observed in segments of the P3HT polymer chain when interacting with PCBM in the ITO/PCBM/P3HT system, but not for ITO/P3MT in the ITO/PCBM/P3MT system. The charge transfer observed between PCBM and P3HT was associated with the stabilization of the radical cation species found in P3HT in this material.